Acute foam rolling effects on contractile properties of the m. biceps femoris: A randomized cross-over pilot study - Schroeder, J.; Renk, V.; Braumann, K. M.; Hollander, K. (German Journal of Exercise and Sport Research, 2017)
Background: Foam rolling (FR) has become a widely-used exercise concept in order to provide muscle restoration. Neurophysiological self-organization processes are considered to explain probable muscle tone modulations. As muscle tone alterations after strength training can be demonstrated using a novel technique (tensiomyography), FR-induced alterations may also be detectable. The present pilot study used tensiomyography (TMG) to analyse the immediate effects on muscle tone after FR and, for comparison purposes, after stretching and weight training. Methods: Following a cross-over protocol, twelve volunteers (6 male; 6 female; age 26.8 ± 5.7 years; body mass index [BMI] 23.1 ± 2.4 kg/m2) completed three different exercise units—FR, stretching and weight training—for the lower back and hip extensor muscles assigned to a randomized order, one session per week. Before and after each session, electrically stimulated muscle displacement (Dm) and contraction time (Tc) was assessed for the biceps femoris muscle using TMG. Results: Dm analyses revealed a significant `time × treatment` interaction (F[1.3, 14.3] = 6.73, p = 0.02). Pre-post comparisons referring to a minimal detectable change (MDC) of 1.2 mm showed relevant Dm changes only after weight training (left: -1.7 mm, right: -1.4?mm). Changes after FR and stretching remained irrelevant (=0.5 mm). For Tc, there was neither a significant `time × treatment` interaction nor any pre-post alteration being greater than the recommended MDC after FR, stretching or strengthening. Conclusions: While muscle tone increased after strength training, relevant changes in muscle tone could not be detected after stretching or FR. As a benefit for practical FR applications, it might be concluded that single bouts of FR are not effectual in significantly affecting muscle tone. However, further research is needed to evaluate expected muscle tone decreases due to myofascial release techniques with varied dose-response conditions (duration, cadence, repetitions or devices).